Historical Analysis of MSMEs in Indonesia: Milestones and Transformation - Hamdani, Hamdani; Sudarmiatin, Sudarmiatin; Rahayu, Wening Patmi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This literature review paper was conducted to observe the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, which have undergone significant transformations over time. By applying a historical analysis framework, the paper traces the evolution of MSMEs in Indonesia, highlighting key milestones, challenges, and the impact of economic policies on their development with the data being gathered from academic journals, government reports (e.g., the Ministry of Cooperatives and MSMEs, Statistics Indonesia), and industry reports from organizations like the Asian Development Bank (ADB). In the pre-independence era, MSMEs were providers of local goods and services, although hindered by exploitative colonial policies. Next, in the Old Order and New Order eras, although MSMEs began to receive attention, the large sector was still prioritized in economic policies. Greater attention to MSMEs emerged after the 1997-1998 crisis, where MSMEs demonstrated extraordinary resilience and became one of the pillars of Indonesia's economy. In the reform era, decentralization allowed MSMEs to develop throughout Indonesia, with increasingly supportive policies such as People's Business Credit (KUR) and entrepreneurship training.